Tampilan Reproduksi Kambing Betina Lokal yang Induksi Berahinya Dilakukan dengan Sistem Sinkronisasi Singkat - Nizwan Siregar, Tongku; Armansyah, Teuku; Sayuti, Arman; -, Syafruddin (Jurnal Veteriner, 2010)
The aim of this study is to determine the reproduction performance of local does in which theirestrous was induced by short synchronization system. In this study 10 healthy female, unpregnant andhave relatively homogenous body weights were used. All does were devided into 2 experiment groups.Group 1 consisted of 4 does as control and group II consisted of 6 does as treatment. Group I, were injectedwith 125 ?g cloprostenol intramuscular, twice in 11 days interval. Group II, was treated with shortsynchronization using 125 ?g cloprostenol intramuscular, and then followed by injection of 300 IU hCGand 0.5 mg estradiol benzoate after 12 hours later. The does were inseminated 10 hours after onset ofestrous and repeated 12 hours later. Parameters measured were oestrous percentage, pregnancy, andlitter size. Results showed that all does (100%) from both groups showed estrous. Percentage of pregnantdoes group I and II were 75.00% and 83.33% respectively, and the averages litter size were 2.0 ± 1.0 and 1.4± 0.3, respetively. Treatment with short synchronization can increase pregnancy and delivered percentagealthough litter size not affected.
Keywords: local goat, short synchronization system, reproduction, estrous induction